Social Construction of the Naqsyabandiyah Tarekat Community in Besilam Village, Langkat Regency, North Sumatra - Putri, Elsa Amanda; Kadarisman, Yoskar (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research attempts to explain the form of social construction carried out by the Naqsyabandiyah congregation on the social world using social construction theory. The Naqshbandiyah order is a path or method that a person takes to get closer to his creator, namely Allah SWT. This research was conducted in Besilam village, Padang Tualang District, North Sumatra Province. The aim of this research is to determine the forms and methods of social construction carried out by the Naqsyabandiyah order on the social world. This research is basic research or basic research in the social field carried out in the field, so the data collection technique was carried out using interview techniques. Subjects in this study were determined using purposive sampling with predetermined criteria. The results of this research are that the Naqshbandiyah congregation has succeeded in carrying out social construction in society and in the social world. The members of the Naqsyabandiyah congregation who underwent an externalization process experienced changes and succeeded in implementing the teachings or values given. The congregation also obeys the adab or rules set by the Naqshbandiyah order through a process of objectification. The internalization process was also successfully established, as evidenced by the survival of the Naqshbandiyah congregation until now and has even experienced development through distribution to various regions, so that congregations outside Besilam can practice the teachings of this congregation.